If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (82 + -4g) = (7g + 5) Remove parenthesis around (82 + -4g) 82 + -4g = (7g + 5) Reorder the terms: 82 + -4g = (5 + 7g) Remove parenthesis around (5 + 7g) 82 + -4g = 5 + 7g Solving 82 + -4g = 5 + 7g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7g' to each side of the equation. 82 + -4g + -7g = 5 + 7g + -7g Combine like terms: -4g + -7g = -11g 82 + -11g = 5 + 7g + -7g Combine like terms: 7g + -7g = 0 82 + -11g = 5 + 0 82 + -11g = 5 Add '-82' to each side of the equation. 82 + -82 + -11g = 5 + -82 Combine like terms: 82 + -82 = 0 0 + -11g = 5 + -82 -11g = 5 + -82 Combine like terms: 5 + -82 = -77 -11g = -77 Divide each side by '-11'. g = 7 Simplifying g = 7
| x^2+x-2441=0 | | 6(x+-126)=-24 | | 2(x+12)=-2(x-12) | | 7-11=-2/5 | | -7a+3+8a=9-27 | | 7x+2=4n+17 | | 2x+77=180 | | -1+6=m-9 | | 3+6=3x | | -4v=42 | | 2(9x-1)=99-7 | | 6cd-4cd= | | 4y+2+15x-1=180 | | 83=2x+6 | | 7.5(x-1)=-0.5x+48.5 | | 9g-s+6a=8g-2a+3fora | | 5.64x+33.84=67.68 | | 8x+7=5x+37 | | 6x-1-4x-8=7x-5x-12 | | 5a+6=2a+15 | | x^2+x-1220=0 | | -i(5-i)+2i(i+6)=0 | | 0=12-2x | | 6(x-3)+2x=30 | | 4ab(a-3b)-3c^2(a-3b)=0 | | 2x^2-12x=-25 | | 5(x+3)=85 | | 2+8i/-5-3i | | 7x/15+1=22 | | -7x+5(-2x-6)=-42-5x | | -3(5d+2)= | | (6x-10)+(2x+12)=180 |